A single-centre, retrospective study of mid-term outcomes of aortic arch repair using a standardized resection and patch augmentation technique. (28th May 2022) - Patukale, Aditya; Shikata, Fumiaki; Marathe, Shilpa S; Patel, Pervez; Marathe, Supreet P; Colen, Timothy; Venugopal, Prem; ,; Alphonso, Nelson
Abstract: OBJECTIVES: The aim of this study was to evaluate the mid-term outcomes after the repair of aortic arch using a standard patch augmentation technique. METHODS: The study included all patients who underwent repair of a hypoplastic/interrupted aortic arch (IAA) in a single institute from June 2012 to December 2019 by a standardized patch augmentation (irrespective of concomitant intra-cardiac lesions). End points evaluated were reintervention for arch obstruction and persistent/new-onset hypertension. RESULTS: The study included 149 patients [hypoplastic aortic arch, n = 92 (62%), IAA, n = 9 (6%), Norwood procedure, n = 48 (32%)]. The patch material used for augmentation of the aortic arch included pulmonary homograft ( n = 120, 81%), homograft pericardium ( n = 18, 12%), CardioCel ® ( n = 9, 6%) and glutaraldehyde-treated autologous pericardium ( n = 2, 1%). The median age and weight at surgery were 7 days [interquartile range (IQR) 5–17 days] and 3.5 kg (IQR 3–3.9 kg), respectively. The median follow-up was 3.27 years (IQR 1.28, 5.08), range (0.02, 8.76). Freedom from reintervention at 1, 3 and 5 years was 95% [95% confidence interval (CI) = 89%, 98%], 93% (95% CI = 86%, 96%) and 93% (95% CI = 86%, 96%) respectively. One patient (0.6%) had persistent hypertension 8 years after correction for interrupted arch with truncus arteriosus. CONCLUSIONS: Repair of hypoplastic/IAA by transection and excision of all ductal tissue and standardized patch augmentation provide good mid-term durability. The freedom from reintervention at 5 years is >90%. The incidence of persistent systemic hypertension following arch reconstruction is low. The technique is reproducible and applicable irrespective of underlying arch anatomy. Abstract : Hypoplasia of the aortic arch ranges from narrowing of the distal arch and isthmus near the insertion of the ductus arteriosus to hypoplasia of the entire aorta.